Stanowisko Hiszpanii wobec NATO w świetle doniesień dziennika „El Pais” z lat 1975-1996 - Domejko-Kozera, Patrycja (Acta Universitatis Lodziensis. Folia Historica, 2008)
When NATO was created in 1949 Spain could not join the organization because of the authoritarian nature of general Francisco Franco regime and its cooperation with fascist Germany and Italy during the II World War. However, the USA recognized the strategic importance of Spanish territory in the period of cold war confrontation and initiated bilateral relations with Madrid in the security policy sphere in 1953. The informal cooperation of Spanish military forces with NATO followed. It was the end of the dictatorship and democratic transformation of the country that enabled Spain’s integration with the organizations of Western world. Once integration with NATO was possible, this issue sharply divided political elites of democratic Spain with the left generally opposing the accession to NATO and the right supporting it. Spain officially became a member of NATO in 1982 but in the same year the socialists came to power with a promise of referendum on the question of Spanish membership in NATO. The socialist government of Felipe González „froze" Spanish integration with this organization but finally pragmatic approach won: it did not lead Spain out of NATO but defined specific conditions of its membership (mainly not joining the integrated military structure). The end of the cold war confrontation and collapse of the USSR resulted in the necessity for NATO to adjust its character and tasks to the new circumstances. González’s government supported this transformation and Spanish forces actively participated in the new missions of NATO, which built Spanish reputation as a credible ally, the symbol of which was the election of Spanish ministry of foreign affairs Javier Solana for the post of Secretary General of the organization.